2020
DOI: 10.1038/s41598-020-66379-x
|View full text |Cite
|
Sign up to set email alerts
|

Long term transcriptional and behavioral effects in mice developmentally exposed to a mixture of endocrine disruptors associated with delayed human neurodevelopment

Abstract: Accumulating evidence suggests that gestational exposure to endocrine disrupting chemicals (EDCs) may interfere with normal brain development and predispose for later dysfunctions. The current study focuses on the exposure impact of mixtures of EDCs that better mimics the real-life situation. We herein describe a mixture of phthalates, pesticides and bisphenol A (mixture N1) detected in pregnant women of the SELMA cohort and associated with language delay in their children. To study the long-term impact of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 65 publications
1
24
0
1
Order By: Relevance
“…Consistent with this idea, it is well-established that NMDAR expression and function are modulated by experience and various environmental factors, including developmental neurotoxins and some therapeutics (Neal et al, 2011;Wills et al, 2012;Alavian-Ghavanini et al, 2018;Repouskou et al, 2020;Engdahl et al, 2021a;Sheng et al, 2022). In addition, GRIN2B is a target for epigenetic control (Rodenas-Ruano et al, 2012;Gulchina et al, 2017;Alavian-Ghavanini et al, 2018;Loureiro et al, 2020;Engdahl et al, 2021a,b;Sheng et al, 2022). It is unclear the extent to which gene × environment interactions determine the symptomatic profile of this disease, but this will be an important avenue for future investigation.…”
Section: Glun2b Variants Limit Synaptic Plasticitymentioning
confidence: 92%
“…Consistent with this idea, it is well-established that NMDAR expression and function are modulated by experience and various environmental factors, including developmental neurotoxins and some therapeutics (Neal et al, 2011;Wills et al, 2012;Alavian-Ghavanini et al, 2018;Repouskou et al, 2020;Engdahl et al, 2021a;Sheng et al, 2022). In addition, GRIN2B is a target for epigenetic control (Rodenas-Ruano et al, 2012;Gulchina et al, 2017;Alavian-Ghavanini et al, 2018;Loureiro et al, 2020;Engdahl et al, 2021a,b;Sheng et al, 2022). It is unclear the extent to which gene × environment interactions determine the symptomatic profile of this disease, but this will be an important avenue for future investigation.…”
Section: Glun2b Variants Limit Synaptic Plasticitymentioning
confidence: 92%
“…Dans la descendance des souris soumises pendant la gestation à une exposition aux perturbateurs endocriniens (BPA, phtalates, pesticides), équivalente à celle d'une cohorte de naissance suédoise, des altérations long terme dans les comportements sont observées avec modification de l'expression de gènes du cerveau. Des altérations similaires du comportement chez le male et la femelle peuvent avoir néanmoins des mécanismes moléculaires et biochimiques sousjacents différents (75).…”
Section: Etudes Expérimentales Modes D'action Et Mécanismesunclassified
“…Benzyl butyl phthalate (BBP) was also reported to modulate the serotoninergic system in the brain of Fundulus heteroclitus (mummichog) [40]. Interestingly, a recent study that better mimics the real-life situation demonstrated that administration of a mixture of phthalates, pesticides, and BPA to mice throughout gestation modified serotonin receptor subtypes 1A and 2A expression in the limbic system of adult offspring animals [41]. These two serotonin receptor subtypes were known to be involved in emotionality and stress coping strategies [42].…”
Section: Effects Of Environmental Chemical Pollutants On the Serotoninergic Systemmentioning
confidence: 99%